Avaliação em matemática no 6º ano do ensino fundamental: formas de ensinar e diferentes tipos de tarefas - OLIVEIRA, Amanda Tamilly Dias de (2023)
This paper presents the methods and practices evaluative of a math teacher in the 6th grade of elementary, in a public school in Bragança, Pará. The main objective is to understand the importance and significance of formative evaluation in the teaching and learning of mathematics, through the investigation of teacher evaluation methods and practices in Elementary School, to make possible the feedback as an exchange of knowledge and evidence to improve quality teaching. The theoric approach used to achieve the proposed objectives implicates the Assessment to Learning, with the support of Fernandes, Luckesi, Hoffmann, and others. The methodology strategies chosen to obtain the information for this research, - of qualitative approach - included classroom observations and a questionnaire with open questions answered by the class teacher, showing his formative experience in the institutions, consistent with the three evaluation stages of the investigated teacher: check in the activities solved by the students, behavior/participation and test. The results show that formative assessment brings positive results in teaching-learning, aiming the student development, through their mistakes, not in a classification way, but as learning. Making it possible to analyze which methods should be followed by the teacher, respecting the needs and individuality of each student.